2014
DOI: 10.1109/jproc.2014.2341554
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Enhanced Information Systems

Abstract: Abstract-Noise, traditionally defined as an unwanted signal or disturbance, has been shown to play an important constructive role in many information processing systems and algorithms. This noise enhancement has been observed and employed in many physical, biological, and engineered systems. Indeed stochastic facilitation (SF) has been found critical for certain biological information functions like detection of weak, subthreshold stimuli or suprathreshold signals through both experimental verification and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 126 publications
(105 reference statements)
4
29
0
Order By: Relevance
“…From Figure 1, M is the minimum detection probability obtained by the noise enhanced Max-min approach. At the same time, M is the achievable maximum of the minimum detection probability in the three different noise-enhanced approaches, which is consistent with the definition given in Equation (13). Additionally, the value of M is independent of τ and With the decrease of τ , the maximum noise-modified average detection probability obtained by the restricted NP approach decreases, and the corresponding value of C increases and approaches M .…”
Section: Numerical Examples and Simulation Analysissupporting
confidence: 82%
See 2 more Smart Citations
“…From Figure 1, M is the minimum detection probability obtained by the noise enhanced Max-min approach. At the same time, M is the achievable maximum of the minimum detection probability in the three different noise-enhanced approaches, which is consistent with the definition given in Equation (13). Additionally, the value of M is independent of τ and With the decrease of τ , the maximum noise-modified average detection probability obtained by the restricted NP approach decreases, and the corresponding value of C increases and approaches M .…”
Section: Numerical Examples and Simulation Analysissupporting
confidence: 82%
“…From Figure 1, M is the minimum detection probability obtained by the noise enhanced Max-min approach. At the same time, M is the achievable maximum of the minimum detection probability in the three different noise-enhanced approaches, which is consistent with the definition given in Equation (13). Additionally, the value of M is independent of τ and M = 0.8988.…”
Section: Numerical Examples and Simulation Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…On the contrary, the positive effect of noise has been paid widespread concern by researchers since Benzi first proposed the concept of stochastic resonance (SR) [2][3][4][5][6][7][8][9]. Some of the more representative studies of SR in signal and information processing are shown as below: a nonlinear bistable autoregressive model applied in signal detection by S. Zozor [4,5], the noise enhanced detection performance under the Neyman-Pearson criterion analyzed by H. Chen [7,8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Such as, the noise enhanced performance of optimal Neyman-Pearson, Bayes and Minimax detectors are studied in [16], which proves that the performance of optimal detectors can be improved by increasing noise level of system under certain conditions. According to Neyman-Pearson criterion, the purpose is to increase the detection probability under the constraint on falsealarm probability [7,8,12]. In [7], a mathematical framework to analyze the noise enhanced effect in binary hypothesis testing problems is developed based on Neyman-Pearson criterion.…”
Section: Introductionmentioning
confidence: 99%